THE EFFECTS OF USING INFORMATION TRANSFER TECHNIQUE TOWARD STUDENTS’ LISTENING COMPREHENSION - Ferri Yonantha; Mohd. Izzat Khan (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
This study aimed to investigate the information about the students’ listening comprehension taught by using Information Transfer technique for experimental class and traditional teaching technique for control class. Then, this study was also to find out whether there was a significant effect of using Information Transfer technique toward students’ listening comprehension. The study used a quasi-experimental-nonequivalent control group design. The participants consisted of two classes of the first-year students of Junior High School, 35 students for experimental class and 35 students for control class. The data were collected by using pre-test before the treatment and post-test after the treatment. The study findings showed that the improvement could be seen from the score test. The result was analyzed statistically by using paired and independent sample t-test through SPSS 16. The result found that there was a significant effect of using Information Transfer toward students’ listening comprehension. Keywords: Information Transfer Technique; Listening Comprehension.